Progressive Steps to Maximize the Payment of Substitute Money in Corruption Crimes - Yasir, Muhammad (West Science Law and Human Rights, 2025)
Although there is a punishment for compensating for state losses brought on by corruption, laws and illegal compensation-paying activities have not been able to efficiently and optimally restore state losses. The study aims to investigate the reasons behind the suboptimal recovery of state losses attributable to corruption through compensation payments, and to identify progressive legislative measures that might enhance the effectiveness of compensation in rectifying these losses.  This study employs a normative research methodology, utilizing secondary data derived from legal texts.  Techniques for acquiring legal information through literature review.   The research results suggest that: 1. The punishment for paying substitute money does not provide the best return of state losses resulting from corruption because: a) there are unclear criminal arrangements for paying substitute money, and b) there are no rules pertaining to the crime of paying substitute money, c) Confiscation Constraints for Payment of Substitute Money, d) Individual Convicts Prefer Subsidiary Prison Instead of Paying Substitute Money, Interpretation of the Purpose of Criminal Application of Substitute Payment Penalties,  and f) PERMA Number 5 of 2014's shortcomings in relation to the charge of using extra replacement money in corruption-related activities.    2. To guarantee that the criminal payment of compensation in corruption may most effectively recoup state losses, the following progressive legislative steps are required:  a) Subsidies are not included in the penalty for paying compensation, b) The existence of the Law on Confiscation and Forfeiture in Corruption Crimes, c) Return of state losses through compensation money taking into account the value of interest, d) Return of state losses through Bankruptcy Efforts or PKPU of Corrupt Corporations,  and e) Corrupt Corporations are restored to Survive and Pay Obligations.